Identification and characterization of a novel HLA‐A allele, HLA‐A*68:105, by genomic sequencing. (15th October 2014) - Curcio, M.; Presciuttini, S.; Sciarrino, R.; Fornaciari, S.; Mariotti, M. L.; Scatena, F.
Summary: A novel HLA‐A allele, HLA‐A*68:105, was detected by sequence‐based typing (SBT) in an Italian bone marrow donor. It differs from HLA‐A*68:01:02 at five nucleotides, three intronic, nt 699 T‐>G (intron 2), nt 705 T‐>C (intron 2) and nt 2770 G‐>A (intron 7), and two located in exon 3, at positions 726 A‐G (codon 94 Ile‐>Val) and 733 T‐G (codon 97 Arg‐>Met), respectively.